OPTIMASI PORTOFOLIO SAHAM MENGGUNAKAN METODE MEAN ABSOLUT DEVIATION BERDASARKAN PENGELOMPOKAN SAHAM MENGGUNAKAN K-MEANS - Fauzan, Nur; Andi Mariani; Nurwahidah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examined the construction of an optimal portfolio using the Mean Absolute Deviation (MAD) method, based on stock grouping through K-Means clustering, and the performance evaluation was conducted using the Sharpe Index method. The aim of this research was to construct an optimal portfolio using the MAD method based on the results of stock selection using K-Means. The analysis resulted in an optimal portfolio that had shown good performance, with a return value of 0.027343086 (or 2.73%) and a risk value of 0.094000665 (or 9.4%).